Analisis Penggunaan Majas pada Lirik Lagu Karya Yuika - Diner, Lispridona; Aprena, Fatih Almas; Pambajeng, Naufal Arya; Nugroho, Muhammad Dimas Seiya; Resi, M. Fadlur (Vocational College of Diponegoro University, 2024)
This article discusses the figures of speech and analyzes the meaning contained in the songs made by Yuika. The purpose of the research is to find out the types of figures and the meaning from the lyrics of Yuika’s songs. This research uses Shigeko Inagaki book “Nihon no Kakikata Retorikku” as its base. The object of this research is four songs in Yuika’s discography. Data collection used listening and note-taking techniques. The analysis method used descriptive method. The results found a total of 18 data. Only four types of figures of speech (Tochihou, Zenshouhou, Tsuikohou, Hanpukuhou) is found. Chokuyuhou and Hangohou were not found in this study. In addition, this study uses association in determining the meaning of the lyrics.